Pengelompokan Barang Menggunakan Metode K-Means Clustering Berdasarkan Hasil Penjualan Di Toko Widya Bengkulu - Achmad Fikri Sallaby; Rizka Tri Alinse; Venny Novita Sari; Tri Ramadani (Jurnal Media Infotama, 2022)
The Widya shop sells various kinds of hijab products that are tailored to the needs of fashion development. The Widya Bengkulu store also sells various kinds of women's needs such as clothes, accessories, bags, wallets, soft lenses, cosmetics and other fancy items. So far, Widya Store has not used computers as a data processing medium. All processes of selling goods and inventory of goods are still carried out with book records, and do not yet have an application that can help the process of managing the data of these goods. In addition, in managing inventory, Toko Widya only sees stock based on sales results, if the stock on one of the items runs out, an order will be made to the supplier. Implementation of the K-Means Clustering Method in Grouping Goods Based on Sales Results at the Widya Bengkulu Store was made using the Visual Basic .Net programming language and SQL Server 2008 database. In the Grouping of Goods Based on Sales Results at the Widya Bengkulu Store, it will be processed to seek knowledge from chunks of data, namely goods sales data. Cluster I is a Very Selling Item, Cluster II is a Self Selling Item, and Cluster III is a Less Selling Item. Based on the results of the tests that have been carried out, the application of Grouping Goods Based on Sales Results at the Widya Bengkulu Store can provide information on the best-selling items sold at the Widya Store.